2010
DOI: 10.14295/rbho.v16i1.517
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento e pós-colheita de abacaxi ornamental

Abstract: RESUMOO presente trabalho foi dividido em duas etapas que tiveram como objetivos, avaliar a durabilidade pós-colheita de Ananas comosus var. erectifolius colhidos em três pontos de colheita, armazenados e refrigerados, bem como determinar o período compreendido entre a indução fl oral ao ponto de colheita. No primeiro experimento, os abacaxis ornamentais foram colhidos em área experimental instalada nas dependências da Embrapa Agroindústria Tropical, em Pacajus -CE. As hastes foram classifi cadas quanto ao com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
0
1
Order By: Relevance
“…Studies carried out in this area show different results in terms of the percentage of institutionalized elderly people with potential drug interactions. Research carried out in Brazil, Greenland and Spain revealed 25.4%, 61.0% and 81.1% of patients, respectively, with potential interactions [53][54][55], although our data showed more than 90% of the sample with potential interactions underscoring the critical need for vigilant drug management in this population. The differences found in potential drug interactions may be due to the assessment tool used.…”
Section: Discussioncontrasting
confidence: 70%
“…Studies carried out in this area show different results in terms of the percentage of institutionalized elderly people with potential drug interactions. Research carried out in Brazil, Greenland and Spain revealed 25.4%, 61.0% and 81.1% of patients, respectively, with potential interactions [53][54][55], although our data showed more than 90% of the sample with potential interactions underscoring the critical need for vigilant drug management in this population. The differences found in potential drug interactions may be due to the assessment tool used.…”
Section: Discussioncontrasting
confidence: 70%